Role of Fine Needle Aspiration Cytology in Effective Management of Patients with Granulomatous Inflammation in Neoplastic and Non-Neoplastic Lesions - Dr. Drashti Patel; Dr. Ashwini Shukla; Dr. Toral Jivani (Tropical Journal of Pathology and Microbiology, 2021)
Background: Granulomatous inflammation is a common diagnosis given in fine-needle aspiration cytology (FNAC) and it is a type of chronic inflammation in which tissue reaction appears following cell injury.Aims: To assess the usefulness of the cytological study in the diagnosis of granulomatous lesions.Materials and Methods: An observational study is done based on cytomorphological evaluation of 156 cases of granulomatous inflammation diagnosed at the Department of Pathology, in Surat Municipal Institute of Medical Education & Research over 18 months from February 2018 to July 2019.Results: Out of the total of 156 cases of granulomatous inflammation, tuberculosis was the most common finding in 111 cases (71.15%), followed by fungal infection (05 cases). The male to female ratio was 1.0 to 1.4. The most commonly affected age group was 21 to 30 years.Conclusions: All the cases of granulomatous inflammations are analysed for definitive diagnosis to provide early and proper treatment of underlying diseases, malignancies or lymphoma.